2012
DOI: 10.1242/jcs.107045
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal TOG domain of Arabidopsis MOR1 modulates affinity for microtubule polymers

Abstract: SummaryMicrotubule-associated proteins of the highly conserved XMAP215/Dis1 family promote both microtubule growth and shrinkage, and move with the dynamic microtubule ends. The plant homologue, MOR1, is predicted to form a long linear molecule with five N-terminal TOG domains. Within the first (TOG1) domain, the mor1-1 leucine to phenylalanine (L174F) substitution causes temperature-dependent disorganization of microtubule arrays and reduces microtubule growth and shrinkage rates. By expressing the two N-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
(66 reference statements)
0
16
0
Order By: Relevance
“…S4), indicating that TOG1 and TOG2 of MOR1 might bind unpolymerized tubulin. However, the N-terminal part of MOR1 containing TOG1 and TOG2 bound sheep brain tubulin very weakly when analyzed by gel filtration (Lechner et al, 2012). We also found that our MOR1 TOG column, containing TOG1 and TOG2, does not bind plant tubulin efficiently.…”
Section: Discussion Tubulin Binding By Tog Domainsmentioning
confidence: 65%
“…S4), indicating that TOG1 and TOG2 of MOR1 might bind unpolymerized tubulin. However, the N-terminal part of MOR1 containing TOG1 and TOG2 bound sheep brain tubulin very weakly when analyzed by gel filtration (Lechner et al, 2012). We also found that our MOR1 TOG column, containing TOG1 and TOG2, does not bind plant tubulin efficiently.…”
Section: Discussion Tubulin Binding By Tog Domainsmentioning
confidence: 65%
“…In the case of the XMAP215 family members, mutating tubulin binding activity in any subset of TOG domains within the array affects tubulin binding and MT polymerization activity with concomitant effects on mitotic spindle size (8,16,17,20,29,42,43). The key to understanding the XMAP215 TOG array MT polymerization mechanism is determining how many tubulin heterodimers the array binds, whether the pentameric TOG array simply tethers tubulin heterodimers or actively potentiates longitudinal or lateral tubulin-tubulin interactions, and what nucleotide and/or conformational state of tubulin each TOG domain in the array preferentially binds.…”
Section: Discussionmentioning
confidence: 99%
“…Mutating the tubulin binding activity of different TOG domains in the pentameric TOG domain array has differential effects on XMAP215 MT polymerization activity and spindle length. Mutations in the TOG1 or TOG2 intra-HEAT tubulin-binding loops compromise XMAP215-mediated MT polymerization activity more dramatically than homologous mutations in TOG3 or TOG4 (8,16,17,20,29,42,43). Mutating the tubulin-binding determinants in TOG5 does not appear to significantly affect the rate of MT polymerization (16,29).…”
Section: Microtubules (Mts)mentioning
confidence: 99%
“…This observation possibly resulted from increased resistance to microtubule destabilizing drugs and bundling typically associated with the 35S pro :GFP-MBD marker (Marc et al, 1998;Lechner et al, 2012). (A) Plus-end velocities of EB1b-GFP of CMTs and EMTs were measured in wild-type and ark1-1 elongating root hairs upon imaging with spinning-disc confocal microscopy.…”
Section: Microtubule Catastrophe Frequency and Growth Rates Are Reducmentioning
confidence: 99%